English Curriculum Development: Teacher Perceptions on Integrating ICT in English Language Teaching - Ginting, Donny Adiatmana; Syarif, Hermawati; Zainil, Yetty (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
In developing an English curriculum, it is important to understand how technology might assist foreign language learning. Besides technology, English teachers have an important role in developing English curriculum because they have the pedagogical ability to formulate the students’ needs. The aim is to reveal the teachers’ perception of integrating technology in English classrooms and its implications to the English curriculum development. The quantitative research approach uses the survey as the research method. The sample are ten English teachers from a few senior high schools in Langkat Regency. The instrument is a questionnaire with fourteen items. The findings are that 82.6% percent English teacher agree that technology learning devices are needed in the English language classroom. Meanwhile, 65.5% agree that interactive applications must be developed in teaching English language. Next, 65.5% of English teacher agree that technology must be involved while teaching the English language. Teacher plays an important role in the English curriculum development because they have pedagogical knowledge to arrange the learning aim as an effort to support students to develop their language skills, critical thinking, and creative thinking, which as the main requirement in 21st learning century and to achieve the aim needs technology.